Intrapleural and Intraperitoneal Free Fluid in Calcium Channel Blocker Overdose - Yilmaz, Mustafa; Ay, Mehmet Oguzhan; Gokel, Yuksel; Kozaci, Nalan; Samanlioglu, Gulnihal; Atli, Mesude; Karakucuk, Seda Nida (Emergency Medicine Physicians Assoc Turkey, 2016)
Aim: Toxicity findings affecting many systems, particularly the cardiovascular system, are observed in calcium channel blocker (CCB) overdose. Here, we aimed to present the incidence of CCB overdose patients with intraperitoneal and intrapleural free fluids detected by abdominal ultrasonography (USG). Materials and Methods: CCB overdose patients admitted to the emergency room in a 2-year period were prospectively included. All patients with CCB overdose were evaluated by bedside abdominal USG in terms of the presence of pleural and peritoneal fluid. Results: A total of 14 patients with CCB poisoning were included in our study. Six (42.8%) patients had taken verapamil, 7 (50%) patients amlodipine, and 1 (7.2%) patient nifedipine. The mean age of the patients was 27.2 +/- 15.9 years (range: 18-65 years). The median time from drug intake to arrival at the hospital was 3.0 h (IQR: 1.75-5). Nine (64.28%) of these patients were detected to have intraperitoneal and intrapleural free fluid by bedside USG. The mean arterial pressure of patients with intraabdominal and intrapleural fluid was lower than that of patients without the detected fluid, i.e., 56.8 (IQR: 54.8-61.8) vs. 65.6 (IQR: 64.2-66.8), respectively (p < 0.001). Conclusion: Besides the cardiovascular findings, intraperitoneal and intrapleural free fluid is also a common feature in CCB overdose. Bedside USG may help to identify these patients.
Keywords: Hypotension; calcium channel blocker; overdose; peritoneal free fluid; pleural free fluid